THE STUDY OF RECRUITMENT AND SELECTION PRACTICES IN ISLAMIC DEVELOPMENT BANK - Fatima Zafar; Abdulquddus Mohammad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The study aimed was to evaluate the effectiveness and efficiency of the recruitment and selection practices in Islamic Development Bank, Jeddah. This study was to find out the challenges allied with recruitment and selection practices and find out ways to help and get better the recruitment and elhuman process in Islamic Development Bank. This study was based on 52 respondents from IDB employees through the use of questionnaires. The results indicated that methods used in recruitment and selection process were effective but time consumption and create difficulties for candidates and HR department. The study also discovered that R & S process were characterized with lots of challenges. The recommendations and suggestions made were that HR department should make the process less time consuming, less costly and be effective and efficient because if right kind of candidate is chosen for right job it may be expensive but the outcome will be higher.